Alcohol consumption and cardiovascular disease, cancer, injury, admission to hospital, and mortality: a prospective cohort study. Issue 10007 (14th November 2015) - Smyth, Andrew; Teo, Koon K; Rangarajan, Sumathy; O'Donnell, Martin; Zhang, Xiaohe; Rana, Punam; Leong, Darryl P; Dagenais, Gilles; Seron, Pamela; Rosengren, Annika; Schutte, Aletta E; Lopez-Jaramillo, Patricio; et al.
Summary: Background: Alcohol consumption is proposed to be the third most important modifiable risk factor for death and disability. However, alcohol consumption has been associated with both benefits and harms, and previous studies were mostly done in high-income countries. We investigated associations between alcohol consumption and outcomes in a prospective cohort of countries at different economic levels in five continents. Methods: We included information from 12 countries participating in the Prospective Urban Rural Epidemiological (PURE) study, a prospective cohort study of individuals aged 35–70 years. We used Cox proportional hazards regression to study associations with mortality (n=2723), cardiovascular disease (n=2742), myocardial infarction (n=979), stroke (n=817), alcohol-related cancer (n=764), injury (n=824), admission to hospital (n=8786), and for a composite of these outcomes (n=11 963). Findings: We included 114 970 adults, of whom 12 904 (11%) were from high-income countries (HICs), 24 408 (21%) were from upper-middle-income countries (UMICs), 48 845 (43%) were from lower-middle-income countries (LMICs), and 28 813 (25%) were from low-income countries (LICs). Median follow-up was 4·3 years (IQR 3·0–6·0). Current drinking was reported by 36 030 (31%) individuals, and was associated with reduced myocardial infarction (hazard ratio [HR] 0·76 [95% CI 0·63–0·93]), but increased alcohol-related cancers (HR 1·51 [1·22–1·89]) and injury (HR 1·29 [1·04–1·61]). High intake was associated with increased mortality (HR 1·31 [1·04–1·66]). Compared with never drinkers, we identified significantly reduced hazards for the composite outcome for current drinkers in HICs and UMICs (HR 0·84 [0·77–0·92]), but not in LMICs and LICs, for which we identified no reductions in this outcome (HR 1·07 [0·95–1·21]; pinteraction <0·0001). Interpretation: Current alcohol consumption had differing associations by clinical outcome, and differing associations by income region. However, we identified sufficient commonalities to support global health strategies and national initiatives to reduce harmful alcohol use. Funding: Population Health Research Institute, the Canadian Institutes of Health Research, Heart and Stroke Foundation of Ontario, AstraZeneca (Canada), Sanofi-Aventis (France and Canada), Boehringer Ingelheim (Germany and Canada), Servier, GlaxoSmithKline, Novartis, King Pharma, and national or local organisations in participating countries.